A [2]pseudorotaxane based on a pillar[6]arene and its application in the construction of a metallosupramolecular polymer. Issue 27 (26th June 2019) - Xia, Danyu; Lv, Xiaoqing; Chen, Kexian; Wang, Pi
Abstract : A novel metallosupramolecular polypseudorotaxane was constructed by pillar[6]arene-based host–guest recognition and metal coordination. Abstract : A novel metallosupramolecular polypseudorotaxane constructed by metal coordination and pillar[6]arene-based molecular recognition was built. First, a [2]pseudorotaxane based on a mono(ethylene oxide) substituted pillar[6]areneP6 and a paraquat derivative guestG was prepared. Then Ag + was used to fabricate the metallosupramolecular polypseudorotaxane based on a metal coordination polymer backbone.